2013
DOI: 10.5897/jpbcs2013.0412
|View full text |Cite
|
Sign up to set email alerts
|

Kernel quality and morphological traits of scented rice (cv. Super Basmati) in relation to irrigation and zinc application

Abstract: Two year field study was conducted at Adaptive Research Farms Sheikhupura and Sargodha with the objective to investigate the impact of irrigation water and zinc application on kernel quality and morphological traits of scented rice, and genotype Super Basmati was selected for this study. Results indicated that increasing applications of irrigation and zinc has positive influence on kernel quality and morphological characters of super basmati, and from two sites data of two growing seasons it was concluded that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Wang et al observed a significant increase in head rice yield, and decrease in kernel chalkiness, length/width ratio, and amylose content as a result of combined application of nitrogen (up to 202.5 kg/hm 2 ), phosphorus (up to 67.5 kg/hm 2 ), and potassium (up to 135.0 kg/hm 2 ) fertilizers. On the other hand, potassium and zinc applications were found to increase amylose content.…”
Section: Impact Of Soil Nutrientsmentioning
confidence: 95%
“…Wang et al observed a significant increase in head rice yield, and decrease in kernel chalkiness, length/width ratio, and amylose content as a result of combined application of nitrogen (up to 202.5 kg/hm 2 ), phosphorus (up to 67.5 kg/hm 2 ), and potassium (up to 135.0 kg/hm 2 ) fertilizers. On the other hand, potassium and zinc applications were found to increase amylose content.…”
Section: Impact Of Soil Nutrientsmentioning
confidence: 95%
“…In contrast to Hasnain and Ali (2013), Ghasal et al (2016) observed that Zn application had no significant impact on amylose content. However, their rates (1.25-5 kg/ ha) were significantly lower (8-14 kg/ha) than the rates used by Hasnain and Ali (2013).…”
Section: The Impact Of Zinc Fertilizer On Rice Grain Qualitymentioning
confidence: 72%
“…(2016) noted that Zn application increased 1,000‐grain weight, which could indicate a change in amylose or amylopectin content as starch accounts for the majority of the grain. In contrast to Hasnain and Ali (2013), Ghasal et al. (2016) observed that Zn application had no significant impact on amylose content.…”
Section: Management Practices Affecting Rice Grain Qualitymentioning
confidence: 76%
See 1 more Smart Citation
“…Relationship between zinc content (g) and grain yield per plant (g) a positive linear relation (R² = 0.2556) between zinc content (g) and grain alylose (%). It was found that amylose content was significantly and linearly increased with increasing zinc application rates (26).…”
Section: Coefficient Of Determinant (R 2 )mentioning
confidence: 97%